Pemikiran Azyumardi Azra Tentang Konsep Negara-Bangsa an Relevansinya terhadap Penguatan NKRI Perspektif Siyasah Dauliyah - Muhammad Zubaily; Syaiful Amri (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines Azyumardi Azra's political thought on the concept of the nation-state and its relevance in strengthening the Unitary State of the Republic of Indonesia (NKRI) from the perspective of Siyasah Dauliyah. This research is motivated by the ongoing debate over the relationship between Islam and the state, particularly the emergence of transnational movements that reject the nation-state system and propose the caliphate as the only legitimate political system in Islam, which threatens the legitimacy of Pancasila and NKRI amidst Indonesia's pluralistic society. Using a qualitative library research method with a descriptive-analytical approach and intellectual history perspective, primary data were obtained from Azra's major works on Islamic politics, democracy, and the relationship between Islam and the modern state. The findings indicate that Azra argues Islam does not prescribe any specific form of state; rather, it provides fundamental principles such as justice, deliberation (shūrā), equality, tolerance, and public welfare. Through a substantive approach to Islam, Azra views the modern nation-state as compatible with Islamic values as long as it promotes social justice, public welfare, and national unity. In the Indonesian context, Pancasila and NKRI are considered consistent with the universal values of Islam and possess historical, constitutional, and moral-religious legitimacy. Azra's thought is highly relevant for strengthening religious moderation, national integration, and resilience against transnational radicalism in Indonesia